Heuristics, irrationality and planning: explained from a “thinking through games” perspective (Ágora de Heterodoxias, 2015)
Using a “thinking through games” perspective to explain the relations between heuristic, irrationality and planning, we reflect and explore social bets on a hazy and uncertain social game of fluid schemes and nonlinear dynamics. We use this same perspective to discuss the required skills and conditions that may facilitate the creation of more efficient and sustainable games.
Keywords: planning; games; heuristic; irrationality